New Faces in a New Place: Long-Time Residents' Perceptions of New Residents in an Oil Boomtown in the Bakken Oil Shale Region. Issue 8 (3rd August 2019) - Huynh, Carol; Robinson, Chloe; Mrozla, Thomas; Dahle, Thorvald O.; Archbold, Carol A.; Marcel, Alexandra
ABSTRACT: In 2008, increased oil production in the Bakken oil shale region in western North Dakota sparked a rapid increase in population for the communities in that area. This study examines long-time residents' perceptions of new residents moving into their community using quantitative methods. The findings reveal that long-time residents who reported an increase in fear of crime because of the oil boom in western North Dakota were less likely to have positive perceptions of new residents. In addition, long-time residents who viewed their community as a friendly place and its residents as trustworthy, and who attempted to interact with new residents, were more likely to report positive perceptions of new residents.